2007
DOI: 10.1002/chem.200701244
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Stereoselectivity in Organocatalysed Reactions with Trimethylsilyl‐Protected Diarylprolinol

Abstract: The origin of the enantioselectivity in the TMS-protected (TMS=trimethylsilyl) prolinol-catalysed alpha-heteroatom functionalisation of aldehydes has been investigated by using density functional theory calculations. Eight different reaction paths have been considered which are based on four different conformers of the TMS-protected prolinol-enamine intermediate. Optimisation of the enamine structures gave two intermediates with nearly the same energy. These intermediates both have an E configuration at the C=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 101 publications
6
46
0
1
Order By: Relevance
“…An even more complex organocatalytic reaction is the one-pot reaction of a,b-unsaturated aldehydes 9 and a tri-carbonyl compound 26 to selectively form four new carbon-carbon bonds, providing six new stereocenters, and thereby 1 out of 64 possible (2 6 ) stereoisomers with excellent diastereo-and enantioselectivity in the product 27 (eqn (12)). 44 The optically active products formed, bicyclo[3.3.1]non-2-enes 27, have a number of important applications and properties as the carbon skeleton in these compounds is a recurrent target in the total synthesis of highly important biomolecules.…”
Section: One-pot Domino and Tandem Reactionsmentioning
confidence: 98%
“…An even more complex organocatalytic reaction is the one-pot reaction of a,b-unsaturated aldehydes 9 and a tri-carbonyl compound 26 to selectively form four new carbon-carbon bonds, providing six new stereocenters, and thereby 1 out of 64 possible (2 6 ) stereoisomers with excellent diastereo-and enantioselectivity in the product 27 (eqn (12)). 44 The optically active products formed, bicyclo[3.3.1]non-2-enes 27, have a number of important applications and properties as the carbon skeleton in these compounds is a recurrent target in the total synthesis of highly important biomolecules.…”
Section: One-pot Domino and Tandem Reactionsmentioning
confidence: 98%
“…[10] Many α-functionalization reactions of aldehydes and ketones have been catalyzed by organocatalysts, including the aldol reaction, [11] the Mannich reaction, [12] amination, [13] oxygenation, [14] fluorination, [15] chlorination, [16] bromination, [17] the Michael reaction, [18][19][20] and so on. By using an enamine catalyst, Beeson et al [9] and Marigo et al [21] recently reported α-fluorination of aldehydes; the transition states of α-fluorination of aldehydes were located by Dinér et al [22] Hayashi et al [23] reported the α-amination [24][25][26][27][28] By using TMS-protected diphenylprolinol as a catalyst, Hayashi et al reported the asymmetric Michael reaction of aldehydes. [24,25] The Michael addition products of acetaldehyde are more useful, as they still contain an active hydrogen atom in comparison to other aldehydes.…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that O-silylated diphenylprolinolderived enamines adopt a preferential conformation in which the substituent at the pyrrolidine ring and the enamine substituent (Me in this case) remain as far as possible from each other in order to avoid steric crowding. [18] On the other hand, indolinecarboxylic acid-derived enamines adopt the opposite conformation in order to minimize steric interactions between the enamine substituent and the a-hydrogen of the aromatic ring ( Figure 1). [19] Having established an optimized protocol, we then proceeded to extend this methodology to other aldehyde donors with different substitution patterns in order to gain further insight into the scope and limitations of the method with regard to the aldehyde substrate (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%